Development of Mathematics Literacy Teaching Module with Problem-Based Learning (PBL) Learning Model - Alayubi, Muh. Algifari; Sappaile, Baso Intang; Upu, Hamzah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2024)
The research method used is Research and Development (R&D) with the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. This research was tested on students of MTs Madani Alauddin and SMP Negeri 3 Sungguminasa. The validation results showed that the teaching module obtained an average score of 4.51, which was classified as valid. The teacher's response to the module was very positive, with a percentage of 93% on the small-scale trial and 94% on the large-scale. The learning implementation observation sheet showed that the module was fully implemented with an average of 1.9 in the small trial and 1.8 in the large trial, so the module was declared practical. Learners' responses were also very positive, with a percentage of 83% in the small trial and 86.6% in the large trial. Learner activities showed high involvement, with 86% in small trials and 88% in large trials. In addition, the learning test results showed the effectiveness of the module with the achievement of 85.3% in the small trial and 91.84% in the large trial. Based on the research results, this teaching module is declared valid, practical, and effective for use in learning mathematics with the PBL model on flat-sided space building material.